2011
DOI: 10.1136/adc.2010.202820
|View full text |Cite
|
Sign up to set email alerts
|

Clinical decision rules for children with minor head injury: a systematic review

Abstract: Of the current decision rules for minor head injury the PECARN rule appears the best for children and infants, with the largest cohort, highest sensitivity and acceptable specificity for clinically significant ICI. Application of this rule in the UK would probably result in an unacceptably high rate of CT scans per injury, and continued use of the CHALICE-based NICE guidelines represents an appropriate alternative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
72
0
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(81 citation statements)
references
References 28 publications
(74 reference statements)
1
72
0
8
Order By: Relevance
“…The validation of (PECARN) was not validated in middle east country before. Our study confirmed the good predictive performances of the PECARN clinical decision rule for minor head trauma in children similar to the previous French study [3,4].…”
Section: Methods and Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The validation of (PECARN) was not validated in middle east country before. Our study confirmed the good predictive performances of the PECARN clinical decision rule for minor head trauma in children similar to the previous French study [3,4].…”
Section: Methods and Resultssupporting
confidence: 90%
“…The risk of ionizing radiation should weighted to the risk of ciTBI. The PECARN rule appears the best for children and infants with the largest cohort and highest sensitivity for detection of ciTBI [2,4]. This study has some limitations which have to be pointed out.…”
Section: Methods and Resultsmentioning
confidence: 85%
“…A recent review of these and other rules applied in pediatric populations concluded that the PECARN rule appears to be the best validated rule for both children and infants. It has the largest study cohort, the highest sensitivity, and acceptable specificity for clinically significant intracranial injuries, although further validation of the PECARN rule is necessary [132].…”
Section: Which Pediatric Patients With Tbi Can Safely Avoidmentioning
confidence: 99%
“…Imaging of paediatric head injuries remains controversial. 4 Several clinical decision rules have been developed to assist in deciding which children would benefit from CT scan imaging. The difficulty lies in balancing the risk to children's developing brains from ionizing radiation against delayed diagnosis of significant brain injury requiring neurosurgical intervention.…”
Section: Introductionmentioning
confidence: 99%